Molecular and Biological Analysis on Ommastrephes caroli Findings in the Central Western Mediterranean Sea (Sardinian Waters) Including First Age Investigation Using Eye Lenses and Beaks - Agus, Blondine; Carugati, Laura; Bellodi, Andrea; Cannas, Rita; Cau, Alessandro; Cera, Jacopo; Coluccia, Elisabetta; Melis, Riccardo; Ruiu, Stefano; Cuccu, Danila (Frontiers in Marine Science, 2021)
Molecular identifications based on two mitochondrial markers (cytochrome c oxidase subunit I -COI- and 16S ribosomal RNA gene -16S-) have been implemented to confirm the morphological identification of eight specimens collected in the Central western Mediterranean. Molecular data show they belonged to a recently resurrected species of the genus Ommastrephes, i.e., O. caroli, known to be distributed in the Atlantic Ocean and Mediterranean Sea. Despite this, molecular analyses of COI sequences evidenced the presence of potential genetic differentiation between Mediterranean and Atlantic samples, highlighting the need for further studies, with more individuals to investigate the connectivity between individuals living in the two areas. Furthermore, morphological, biometric and reproductive features here reported, could be useful in evaluating possible distinctive biological features between the Mediterranean and Atlantic individuals. Female mature size was larger than the male. The relationships obtained between the beak measurements and body sizes (DML; TW) were better described by a power model. Asynchronous oocytes development with relatively small oocytes (0.05-1.10 mm) and a protracted intermittent spawning with active feeding were observed. This study also reported for the specie O. caroli the first data on the potential fecundity estimated (840061 oocytes), the oviducal load (90000 ripe oocytes) as well as the number of seminal receptacles and the size and morphology of the spermatangia found in the buccal mass of all mated females. Even if on a low sample size, beaks and eye lenses were used for the first time in O. caroli for age estimation. The statistically significant relationship found between increments counted in eye lenses and beaks highlighted the reliability of the lenses to estimate age in O. caroli, even if further studies will be needed for its validation. Assuming a daily increment for both structures, a mean life span of about 12-13 months was estimated for both sexes, which is consistent with the sexual maturity condition observed in all the samples and the semelparity known for cephalopods coleoids.